Associations of composite dietary antioxidant index with premature death and all-cause mortality: a cohort study - Huiqin Zhong; Ya Shao; Xin Chen; Na Wang; Yan Zhan; Boxiong Gong; Rong Zhang; Longti Li (BMC Public Health)
Abstract Although previous evidence indicates that the composite dietary antioxidant index (CDAI) is negatively associated with health outcomes, no studies have explored the association between CDAI and premature death. This research utilized a cohort study design with 37,301 participants from the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2018. Cox proportional hazard regression was employed to analyze the association between CDAI and premature death and all-cause mortality. Restricted cubic spline (RCS) analysis was performed to examine the nonlinear relationship between variables, and Kaplan-Meier analysis was used to evaluate survival outcomes over time. Sensitivity and subgroup analyses were conducted to assess the reliability of the findings. During a median follow-up period of 8.25 years, 4487 deaths were recorded, with 1671 classified as premature. The study revealed a negative correlation between CDAI and premature death (Per-SD hazard ratio [HR] 0.91, 95% CI 0.85–0.97; quartiles [Q4:Q1] HR 0.83, 95% CI: 0.70, 0.98) as well as all-cause mortality (Per-SD HR 0.96, 95% CI 0.92-1.00; quartiles [Q4:Q1] HR 0.91, 95%CI: 0.82, 1.01). The RCS analyses indicated a ‘U’ shaped relationship between CDAI and premature death and all-cause mortality. The threshold effect analysis pinpointed the inflection points for CDAI relative to premature death and all-cause mortality at 1.42 and 1.48, respectively. Kaplan-Meier curves illustrated that the likelihood of individual survival increases with higher CDAI quartiles. The results highlight the significance of dietary antioxidant intake in enhancing extending lifespan. Further research is needed to investigate the underlying mechanisms and determine optimal intake levels for improving health outcomes.